Acylsilanes in Iridium‐Catalyzed Directed Amidation Reactions and Formation of Heterocycles via Siloxycarbenes. Issue 51 (5th November 2015) - Becker, Peter; Pirwerdjan, Ramona; Bolm, Carsten
Abstract: Exposing ortho‐amido aroylsilanes to visible light or heat leads to cyclization reactions that provide N‐heterocyclic compounds via siloxycarbenes as key intermediates. The previously unreported starting materials have been prepared by directed amidations of aromatic acylsilanes in the presence of an iridium catalyst followed by N‐alkylation. Abstract : Getting around : The ortho ‐amidation of aroylsilanes with sulfonyl azides in the presence of an iridium catalyst occurs in a highly efficient manner with broad tolerance to substituents on all the reaction partners. After N‐functionalization, the products can undergo photochemically or thermally induced cyclization reactions to give N‐heterocyclic compounds in high yields.